2014
DOI: 10.1371/journal.pone.0109106
|View full text |Cite
|
Sign up to set email alerts
|

PssP2 Is a Polysaccharide Co-Polymerase Involved in Exopolysaccharide Chain-Length Determination in Rhizobium leguminosarum

Abstract: Production of extracellular polysaccharides is a complex process engaging proteins localized in different subcellular compartments, yet communicating with each other or even directly interacting in multicomponent complexes. Proteins involved in polymerization and transport of exopolysaccharide (EPS) in Rhizobium leguminosarum are encoded within the chromosomal Pss-I cluster. However, genes implicated in polysaccharide synthesis are common in rhizobia, with several homologues of pss genes identified in other re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…Recent research supports the presence of multi-protein interactions in the Wzy-dependent pathway (Marczak et al, 2013(Marczak et al, , 2014Marolda et al, 2006). Woodward et al (2010) purified Escherichia coli O86 (Wzy Ec ) and showed using an in vitro assay that Wzz and Wzy are sufficient to determine the Oag modal chain length.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent research supports the presence of multi-protein interactions in the Wzy-dependent pathway (Marczak et al, 2013(Marczak et al, , 2014Marolda et al, 2006). Woodward et al (2010) purified Escherichia coli O86 (Wzy Ec ) and showed using an in vitro assay that Wzz and Wzy are sufficient to determine the Oag modal chain length.…”
Section: Introductionmentioning
confidence: 93%
“…Marczak et al (2013) showed by using a bacterial two-hybrid system that the Rhizobium leguminosarum PssP, which is a PCP, interacts with PssL and PssT, which are Wzx and Wzy proteins, respectively. Recently, they again showed that the PssP2 protein, which is also a PCP, interacts with PssT using a bacterial two-hybrid system (Marczak et al, 2014). However, to date there is a lack of evidence on the interaction of Wzy with other proteins of the Wzy-dependent Oag biosynthesis pathway using more direct approaches.…”
Section: Introductionmentioning
confidence: 99%
“…A mutation in pssM resulted in failed symbiosis with the compatible host plant. Moreover, some genes involved in EPS polymerization and export were characterized (pssTNOP, pssL and pssP2), among them a majority are located in the polysaccharide synthesis region (Mazur et al 2005;Marczak et al 2013Marczak et al , 2014.…”
mentioning
confidence: 99%
“…A mutant in the pssP2 gene localized within the Pss-II region in R. leguminosarum bv. trifolii [ 14 ] produced more EPS than the wild type strain, with predominating HMW fractions with molecular mass exceeding respective ones in the wild type strain [ 37 ]. PssP2 has been shown to interact with glycosyltransferase PssC and PssP/PssT proteins.…”
Section: Introductionmentioning
confidence: 99%